Theoretical risk ranking of commonly consumed processed Philippine fish species with and without phosphorus-containing additives - Azanza, Maria Patricia V.; Bautista, Karina Angela D.; Azarcon, Vallerie B. (2018)
A framework of theoretical calculations based on the review of published information was used to determine possible risks due to dietary phosphorus in identified commonly consumed Philippine fish species ? including tilapia, milkfish, round scad, and yellowfin tuna. The reported individual consumption data and mean body weight of various age groups starting from preschool (6 mo ? 5 y/o) to elderly (≥60 y/o) in the Philippines, the standardized maximum tolerable daily intake of phosphorus, and the phosphorus levels in EP of fish species were utilized to calculate worstcase scenario risk values. The background phosphorus levels of fish species were based on their corresponding reported natural mineral content, while total phosphorus content was calculated from the background phosphorus in addition to the allowable maximum guideline value for phosphorus additive in processed fish products. Theoretical results showed that all age groups are at low risk in the consumption of the identified fish species, with or without phosphorus-containing additives, based on the ranking. The study recommended the validation of the framework of calculation by its application to other food additives. A supplemental study for the validation of the background phosphorus levels in raw test fish species and the total phosphorus levels in processed products with the additive commercially sold in the market was also recommended.